Arabinoxylan content and grain tissue distribution are good predictors of the dietary fibre content and their nutritional properties in wheat products. (30th October 2020) - Barron, Cécile; Bar-L'Helgouac'h, Christine; Champ, Martine; Saulnier, Luc
Highlights: Arabinoxylan content in wheat products is highly correlated to TDF content. The amount of AX released by a xylanase is not simply related to TDF content in wheat products. The amount of AX released by xylanase is proposed as a functional evaluation of DF in wheat products. Abstract: Wheat millstreams and wheat-based foods (pasta, biscuits and bread) enriched or not in dietary fibre with fractions extracted from wheat grains, have been characterized either for their total dietary fibre content (TDF) and their arabinoxylan (AX) content. A strong correlation (r 2  = 0.98) is observed between the AX and TDF contents indicating that AX can be used to estimate TDF content in wheat products. Moreover, by adding a previous step including enzymatic hydrolysis with a xylanase, a functional evaluation of DF is proposed based on the amount of AX released by the enzyme. Xylanase hydrolysable AX are likely also released by microbiota's enzymes in the gut and therefore an indicator for the proportion of fermentable DF in grain fractions and wheat-based foods (pasta, biscuits and bread). This assay opens the door for simple characterization of qualitative attribute of cereal DF.